Internal Control and Internal Control System: On the Issue of Defining Principles in the Context of International Business - Shum, Alina (Global Scientific Trends, 2025)
The purpose of the article is to investigate, generalize, systematize, and classify the principles of internal control and the internal control system, as well as the construction and functioning of the internal control system, using examples from industrial enterprises and those operating in international business within the sphere of international economic relations. However, as the conducted studies have shown, their results-subject to certain transformations and accounting for specific features-can be extended to enterprises in other sectors of the economy. One of the most significant trends clearly emerging at the current stage of economic development is the comprehensive improvement of management quality at all levels. Key components of this process include enhancing the quality of control and the information used for managerial decision-making. This necessitates higher demands on the development of control theory and management theory as a whole to support practical business activities. In the course of the research, the main approaches to one of the key issues in internal control theory-the principles of internal control and the principles of the internal control system-were examined and summarized. As the studies revealed, there is currently no unified viewpoint among specialists and practitioners in control and management activities, as well as experts in management and international management, regarding the composition, content, and classification of the principles of internal control and the internal control system. As a result of the research, the composition and content of the principles of internal control and the internal control system were refined. A number of new principles were proposed that could enhance the practical component of the internal control system and positively impact the development of control and management theory as a whole, as well as management theory at all levels, including international management. The outcome of the research was a classification of the principles of internal control and the principles of the internal control system.
Keywords: principle; internal control system; internal control; control; audit; management; international business; international management